Language Appropriation and Cultural Reconstruction: An example of Morrison’s Song of Solomon - Boukhalkhal, Yassmine (LANGUAGE ART, 2021)
Cultural fragmentation as a result of collective trauma evokes the question of representation as a means of identification during conflict. In the period of intellectual revolution, language lies at the core of the problem since speaking is the negation of silence and silencing. The question of the appropriate way to express and reclaim one’s past, culture, and identity falls within the scope of historical constructors/ re-constructors’ negotiations. While some of them, including Ngũgĩ wa Thiongʼo, suggest writing in national and ethnic languages for the sake of their people, others like Chinua Achebe prefer writing in the dominator’s language to display and prove the culture of the dominated through creating an international discourse. However, the latter standpoint calls also for a New Language that is guilt-free using language appropriation. Toni Morrison’s Song of Solomon is worth pointing at work to illustrate the significance of language appropriation. Morrison assumes a kind of escape, a spiritual one, embedded in language. Milkman, the protagonist, has an identity that is split spatially as Homi Bhabha labels that. While his identity must just match his social reality, Milkman is stuck in the after effects of cultural identification. As a result, in order to piece together his fragmented reality, he must fly back to his origins. During his journey, he learns about the past through an encoded song, Song of Solomon. Although the lyrics are mostly written in English in addition to some African dialects, the song sounds like nonsense while it bears cultural connotations. Thus, language is used within a specific context that makes it able to cope with the signified.